Ocorrência de pseudovaríola na microrregião de Viçosa - Ribeiro , M F B; Belém , P A D; Bicudo , P L (Revista Ceres, 2025)
This paper describes the occurrence of three outbreaks of vesicular disease of the udder of cows in dairy cattle in the Microregion of Viçosa, State of Minas Gerais.